Neural mechanisms of internal distraction suppression in visual attention. (August 2019) - Rajan, Abhijit; Meyyappan, Sreenivasan; Walker, Harrison; Henry Samuel, Immanuel Babu; Hu, Zhenhong; Ding, Mingzhou
Abstract: When performing a demanding cognitive task, internal distraction in the form of task-irrelevant thoughts and mind wandering can shift our attention away from the task, negatively affecting task performance. Behaviorally, individuals with higher executive function indexed by higher working memory capacity (WMC) exhibit less mind wandering during cognitive tasks, but the underlying neural mechanisms are unknown. To address this problem, we recorded functional magnetic resonance imaging (fMRI) data from subjects performing a cued visual attention task, and assessed their WMC in a separate experiment. Applying machine learning and time-series analysis techniques, we showed that (1) higher WMC individuals experienced lower internal distraction through stronger suppression of posterior cingulate cortex (PCC) activity, (2) higher WMC individuals had better neural representations of attended information as evidenced by higher multivoxel decoding accuracy of cue-related activities in the dorsal attention network (DAN), (3) the positive relationship between WMC and DAN decoding accuracy was mediated by suppression of PCC activity, (4) the dorsal anterior cingulate (dACC) was a source of top-down signals that regulate PCC activity as evidenced by the negative association between Granger-causal influence dACC→PCC and PCC activity levels, and (5) higher WMC individuals exhibiting stronger dACC→PCC Granger-causal influence. These results shed light on the neural mechanisms underlying the executive suppression of internal distraction in tasks requiring externally oriented attention and provide an explanation of the individual differences in such suppression.